Analysis of Language Errors in Letters from Readers of Hidayatullah Magazine 2023 Edition - Setiyono, Joko; Sholehhudin, Muhammad; Ulfaida, Nabila (IKIP PGRI Bojonegoro, 2024)
This research was carried out with the aim of describing several things, namely (1) describing and explaining language errors from the use of capital letters in writing Reader's Letters in the 2023 edition of Hidayatullah Magazine, (2) describing and explaining language errors in writing words in Reader's Letters in the Magazine Hidayatullah 2023 edition, (3) describes and explains language errors in the use of punctuation marks in the Reader's Letter in the 2023 edition of Hidayatullah Magazine. This research uses a qualitative descriptive research design. The data for this research is in the form of Reader Letters in the 2023 edition of Suara Hidayatullah magazine. The method in this research is the observation method. This data was collected through observation. The data collection technique used was reading and note-taking. In collecting data, the researcher read the Reader's Letter and then observed language errors according to the spelling level, especially errors in the use of capital letters, errors in writing words, and errors in the use of punctuation marks. To maintain the validity of the data, data triangulation activities were carried out. Data analysis activities start from the data review stage, data identification and classification stage, and data evaluation stage.